Empowering Islamic Senior High School through Educational Technology: A Case Study of MA Al Irtiqo’ Malang - Srikandi Kusumaning Pertiwi, Diajeng; Dwi Anggun Lestari, Nyimas; Renni Hasibuan (INTIFA: Journal of Education and Language, 2025)
The integration of technology in education is a critical step for madrasahs to remain relevant in the digital era. Madrasah Aliyah (MA) Al Irtiqo has undergone a digital transformation by utilizing various technological tools such as laptops, televisions, projectors, smartphones, and digital applications to support both academic and extracurricular activities. However, challenges such as limited device availability, uneven infrastructure distribution, and unstable internet connections still persist. This study aims to explore the implementation of educational technology at MA Al Irtiqo, the benefits and limitations experienced, and strategic recommendations for sustainable integration. The research method used is qualitative descriptive through observation and documentation analysis. The findings reveal that technology is effectively used in classrooms and extracurricular programs to enhance student creativity, digital literacy, and collaborative learning. Nevertheless, infrastructural constraints reflect the early-stage adaptation process common in madrasah environments. This study is relevant to the development of national education policy to ensure equitable technological advancement in religious-based schools. Future research is recommended to quantitatively evaluate the impact of technology on student outcomes and conduct comparative studies across madrasahs to identify best practices in digital learning implementation.